5(3x+1)=2(5x-4)+6x

Simple and best practice solution for 5(3x+1)=2(5x-4)+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3x+1)=2(5x-4)+6x equation:


Simplifying
5(3x + 1) = 2(5x + -4) + 6x

Reorder the terms:
5(1 + 3x) = 2(5x + -4) + 6x
(1 * 5 + 3x * 5) = 2(5x + -4) + 6x
(5 + 15x) = 2(5x + -4) + 6x

Reorder the terms:
5 + 15x = 2(-4 + 5x) + 6x
5 + 15x = (-4 * 2 + 5x * 2) + 6x
5 + 15x = (-8 + 10x) + 6x

Combine like terms: 10x + 6x = 16x
5 + 15x = -8 + 16x

Solving
5 + 15x = -8 + 16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16x' to each side of the equation.
5 + 15x + -16x = -8 + 16x + -16x

Combine like terms: 15x + -16x = -1x
5 + -1x = -8 + 16x + -16x

Combine like terms: 16x + -16x = 0
5 + -1x = -8 + 0
5 + -1x = -8

Add '-5' to each side of the equation.
5 + -5 + -1x = -8 + -5

Combine like terms: 5 + -5 = 0
0 + -1x = -8 + -5
-1x = -8 + -5

Combine like terms: -8 + -5 = -13
-1x = -13

Divide each side by '-1'.
x = 13

Simplifying
x = 13

See similar equations:

| 27(1.4+1.2)-26(1.4+1.2)= | | -65.375=7.2(9c+1) | | (2x+9)+(2x+8)+(2x)=(2x)+(3x+1) | | 2a/3+1/5 | | 7/3x+9/6x=36/9 | | 10y=12.6 | | -3a+4=-8 | | 6(3x-2)=18x-12 | | 4x^2+19x+22=0 | | 35=45 | | (-2/7)(2m+6)=(1/28)m-11 | | x+15+2x=-5-2x-30 | | -14-4(x)=-58 | | 6(2x+6)= | | 8y+3(y-5)=6(y+1)-3 | | 40/x-40x+39=0 | | 2(3x-6)+5=12-(x+5) | | r-3/7r=98000 | | (8x^2-3x^3)-(5x^2-9x^3)= | | 4556776+455556= | | 4.2+10m=6.75 | | (1/4)d-(2/5)=(3/4)d+11 | | 10=a-7 | | x^2-(6x)=13 | | 7x+2x(x+6)=39 | | x+5.2=-6.5 | | 15(p^2-1)-16p=0 | | -4=-7x | | 0.1+1.4=1.2x-3 | | 10x+18=4x+60 | | 17/2y=-17 | | 8+3(s-6t)= |

Equations solver categories